PENERAPAN KEPEMIMPINAN INSTRUKSIONAL DALAM KEPEMIMPINAN KEPALA MADRASAH PADA MAN 2 BULUKUMBA - Sulaeha, Rina (Idaarah: Jurnal Manajemen Pendidikan, 2019)
The purpose of this study was to find out how the strategies and opportunities and challenges of instructional leadership of Madrasah Aliyah Negeri 2 Bulukumba Headmaster. Research is a descriptive qualitative research with a pedagogical, sociological and philosophical approach. The data collection techniques used are observation, interview and documentation. The results of the study found that 1) Instructional Leadership of Madrasah Aliyah Negeri 2 Bulukumba went well but the need for policy innovations is to present the campus in Madrasah internal supervision and training activities, 2) Instructional Madrasah Head Instructional Strategy that is implemented is to maximize supervision of Madrasah scope, training the scope of Madrasas and involving teachers and education staff training/workshops/seminars to improve the quality of education in Madrasas in quantity but not yet maximally in quality because internal training and supervision has not been maximized because it has not involved experts in their fields, namely the campus, 3) Opportunities and challenges of the Head Madrasah Aliyah Negeri 2 Bulukumba in implementing instructional leadership are 1) Opportunities: (a) Maximum support for teaching and educational staff in order to improve the quality of education, (b) Madrasas have partners who can work together to To improve the quality of education in Madukah Aliyah Negeri 2 Bulukumba, (c) Budgeting for increasing human resource competency in Madarasah Aliyah Negeri 2 Bulukumba. 2) Challenges: (a) The portion of the budget is divided so that it cannot maximally develop and improve HR in Madrasahs, (b) Mitra MadarasahAliyah Negeri 2 Bulukumba has not formed a partnership with the campus which is considered to be able to improve the quality of human resources, (c) Educators and education staff have not maximally made individual efforts to improve their performance.